The Influence Of Market Orientation, Innovation, And Entrepreneurship On Marketing Performance: A Case Study Of Pecel Lele Msmes At Oku Timu - Tokingli Indomarco; Rhian Indradewa (Publikasi Indonesia, 2023)
This study analyses market orientation, product innovation, and marketing performance toward competitive advantage. The population used in this study is Pecel Lele MSME actors in East Oku Regency. The number of samples used in this study was 105 respondents. The method of data collection is done through a questionnaire. This study uses Structural Equation Modeling (SEM) with the SmartPLS Software Program analysis tool. The results of this study indicate that market orientation has a positive and significant effect on competitive advantage, product innovation has a positive and significant effect on competitive advantage, and marketing performance has a positive and significant effect on competitive advantage, market orientation has a positive and significant effect on marketing performance, product innovation has a positive and significant effect on marketing performance, entrepreneurial orientation has a positive and significant effect on marketing performance, and competitive advantage has a positive and significant effect on marketing performance